Auditory evoked fields elicited by spectral, temporal, and spectral-temporal changes in human cerebral cortex - Okamoto, Hidehiko; Teismann, Henning; Kakigi, Ryusuke; Pantev, Christo (Frontiers in Psychology, 2012)
Natural sounds contain complex spectral components, which are temporally modulated as time-varying signals. Recent studies have suggested that the auditory system encodes spectral and temporal sound information differently. However, it remains unresolved how the human brain processes sounds containing both spectral and temporal changes. In the present study, we investigated human auditory evoked responses elicited by spectral, temporal, and spectral-temporal sound changes by means of magnetoencephalography (MEG). The auditory evoked responses elicited by the spectral-temporal change were very similar to those elicited by the spectral change, but those elicited by the temporal change were delayed by 30 – 50 ms and differed from the others in morphology. The results suggest that human brain responses corresponding to spectral sound changes precede those corresponding to temporal sound changes, even when the spectral and temporal changes occur simultaneously.